An Investigation of the Capabilities of Resin Tire Carbon Black “N-330” as a Waste Binder in Asphalt Concrete Mixtures - Amr. A. Nada; Walid Fouad Edris; Hebah Mohammad Al-Jabali; Ahmed D. Almutairi; Abd Al-Kader A. Al Sayed; Shady Khairy (Buildings)
This study investigates the potential use of tire-derived carbon black “N-330” as a sustainable waste binder in asphalt concrete mixtures, combined with resin as an alternative to the usual binding material in asphalt mixtures, “bitumen”. With the increasing demand for environmentally friendly construction materials, this research aims to assess the feasibility of incorporating resin tire carbon black N-330 “RTCB N-330” into asphalt as a full replacement for conventional binders. A comprehensive experimental program has been designed to evaluate the mechanical and performance properties of asphalt mixtures containing varying proportions of RTCB N-330, ranging from 2% to 10% by weight of the binder. The impact of replacing bitumen with resin that contains TCB N-330 on the physical, rheological, and thermal characteristics of RTCB N-330 as a modified asphalt binder is assessed in this study. To assess the binders, a number of tests were carried out, including standard tests for ductility, the softening point, and penetration. DTG (Derivative Thermogravimetric Analysis) and testing the thermal susceptibility index were performed. A higher percentage of TCB N-330 reduced the penetration while increasing both the softening point and ductility. Resin with 8% of TCB N-330 was the optimum percentage, which was compared with bitumen as a new environmentally friendly binder. The testing program involved the preparation of asphalt concrete specimens using a Marshall mix design, followed by a Marshall Stability test to evaluate the deformation resistance of the modified mixtures. The results were anticipated to demonstrate that incorporating N-330 into asphalt mixtures can enhance stability. The Marshall test results indicated that samples with 6% resin tire carbon black as the binder percentage “AC-RTCB6” demonstrated the highest stability among all RTCB samples. Moreover, these samples outperformed asphalt mixtures using bitumen as the binder in terms of stability. Also, the AC-B mixes exhibited lower flow values compared to the AC-RTCB mixes. The higher flow observed in the AC-RTCB specimens suggests that the addition of 1.5% xylene as a solvent to the resin was effective and positively influenced the flow characteristics.